Controlling Fraud in Small Business Health Benefits Programs in the United States, 1990-1996 - Tillman, Robert ([Verlag nicht ermittelbar], 1999)
The focus of this project was insider fraud -- crimes committed by the owners and operators of insurance companies that were established for the purposes of defrauding businesses and employees. The quantitative data for this collection were taken from a database maintained by the National Association of Insurance Commissioners (NAIC), an organization that represents state insurance departments collectively and acts as a clearinghouse for information obtained from individual departments. Created in 1988, the Regulatory Information Retrieval System (RIRS) database contains information on actions taken by state insurance departments against individuals and firms, including cease and desist orders, license revocations, fines, and penalties imposed. Data available for this project include a total of 123 actions taken against firms labeled as Multiple Employer Welfare Arrangements or Multiple Employer Trusts (MEWA/MET) in the RIRS database. Variables available in this data collection include the date action was taken, state where action was taken, dollar amount of the penalty imposed in the action, and disposition for action taken.